Stand-Alone Lateral Interbody Fusion for the Treatment of Low-Grade Degenerative Spondylolisthesis. (1st April 2012) - Marchi, Luis; Abdala, Nitamar; Oliveira, Leonardo; Amaral, Rodrigo; Coutinho, Etevaldo; Pimenta, Luiz
Abstract : The purpose of this paper was to investigate the stand-alone lateral interbody fusion as a minimally invasive option for the treatment of low-grade degenerative spondylolisthesis with a minimum 24-month followup. Prospective nonrandomized observational single-center study. 52 consecutive patients (67.6 ± 10  y/o; 73.1% female; 27.4 ± 3.4  BMI) with single-level grade I/II single-level degenerative spondylolisthesis without significant spine instability were included. Fusion procedures were performed as retroperitoneal lateral transpsoas interbody fusions without screw supplementation. The procedures were performed in average 73.2 minutes and with less than 50cc blood loss. VAS and Oswestry scores showed lasting improvements in clinical outcomes (60% and 54.5% change, resp.). The vertebral slippage was reduced in 90.4% of cases from mean values of 15.1% preoperatively to 7.4% at 6-week followup (P < 0.001 ) and was maintained through 24 months (7.1%, P < 0.001 ). Segmental lordosis (P < 0.001 ) and disc height (P < 0.001 ) were improved in postop evaluations. Cage subsidence occurred in 9/52 cases (17%) and 7/52 cases (13%) spine levels needed revision surgery. At the 24-month evaluation, solid fusion was observed in 86.5% of the levels treated. The minimally invasive lateral approach has been shown to be a safe and reproducible technique to treat low-grade degenerative spondylolisthesis.